BIẾN THIÊN THEO THỜI GIAN CỦA NỒNG ĐỘ ĐIỆN TỬ TỔNG CỘNG VÀ NHẤP NHÁY ĐIỆN LY THEO SỐ LIỆU GPS LIÊN TỤC Ở VIỆT NAM - Lan, Trần Thị; Minh, Lê Huy (Vietnam Journal of Earth Sciences, 2012)
Temporal variations of the total electron content and ionospheric scintillation from the continuous GPS data in Vietnam Vietnam lies in the equatorial region, encompasses the latitude region from about 8°30’N to 23°30’N geographical latitude (0°30’N to 15°30’N geomagnetic latitude). To study the ionosphere in the equatorial region, in the framework of the scientific co-operation between the Institute of Geophysics (Vietnam) and University of Rennes 1 and National School of Telecommunication of Brest (France), three dual frequency GPS receivers were installed in Vietnam since April 2005: at Hanoi (21°02N) - a station under the equatorial ionospheric anomaly crest, at Hue (16°27N) - a station near the anomaly crest region, and at Ho Chi Minh city (10°50N) - an equatorial station. This paper presents the studied results of the temporal variations of the total electron content (TEC) and ionospheric scintillation using the GPS continuous data in Vietnam during the low solar activity period of 2005-2008. These results show that: the diurnal variation in TEC is reach of one maximum value around 14h LT and one minimum value at 5h LT, the occcurent of scintillation as a function of time in the day, almost occurs at night time in this region. Both of TEC and ionospheric scintillation present the seasonal variation, peaking on equinox months. The studied results also show the dependence of TEC and ionospheric scintillation on the solar activity and the observation stations.